2021
DOI: 10.1002/acn3.51375
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the acute pentylenetetrazole‐induced seizure paradigm and a literature review

Abstract: Objective: To confirm the critical factors affecting seizure susceptibility in acute pentylenetetrazole (PTZ) mouse epilepsy models and evaluate the prior literature for these factors. Methods: Serial cohorts of wild-type mice administered intraperitoneal (IP)-PTZ were aggregated and analyzed by multivariate logistic regression for the effect of sex, age, background strain, dose, and physiologic stress (i.e., EEG implantation and/or single-housing) on seizure response. We assessed the reporting of these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(89 reference statements)
0
8
1
Order By: Relevance
“…Interestingly, female mice took less time to develop a generalized convulsive seizure and had a higher seizure severity when compared to males, contrary to previous reports that found no difference between sexes ( Yuskaitis et al, 2021 ). This may be due to the use of different strains, age and physiologic stressors between studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, female mice took less time to develop a generalized convulsive seizure and had a higher seizure severity when compared to males, contrary to previous reports that found no difference between sexes ( Yuskaitis et al, 2021 ). This may be due to the use of different strains, age and physiologic stressors between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be explained by differences in the age at time of injury (i.e., pediatric compared to adult) as pediatric populations respond differently to TBI, have a higher incidence of PTE, and are more likely to develop post-traumatic seizures compared to older groups ( Hwang et al, 2019 ; Webster et al, 2019 ; Elsamadicy et al, 2021 ; Mariajoseph et al, 2022 ). It may also be explained by differences in strain and methodologies used, as murine strains present diverse responses to PTZ, responses can vary between injury models, lower PTZ dosage can result in a greater proportion of subconvulsive events, epileptogenic sequelae vary with the stage of recovery being assessed, and physiologic stressors including EEG implantation and single-housing can increase the number of PTZ-induced seizures ( Bolkvadze and Pitkänen, 2012 ; Mukherjee et al, 2013 ; Smith et al, 2018 ; Yuskaitis et al, 2021 ). Furthermore, although no effect of TBI on response to PTZ was evident at this timepoint, it is possible that the CCI was still pro-epileptogenic in terms of the development of spontaneous seizures.…”
Section: Discussionmentioning
confidence: 99%
“…This study was concerned with the effect of crude alkaloids extract of MC on the behavior alteration and the level of brain neurotransmitters GABA and glutamate in chicks PTZ-induced convulsions. PTZ is often used to induce the development and study of convulsions, as well as, it is used to evaluate the potential efficacy of antiepileptic substances in experimental animals (23). The results of the study showed that the treatment of chicks by PTZ exhibited obvious convulsive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…injected with 65 mg/kg PTZ during the light phase of the light-dark cycle. Mice were monitored by an investigator blinded to genotype and treatment for generalized tonic-clonic seizures over a 20-min period, as previously described (Yuskaitis et al, 2021). After the 20-min observation period, mice were sacrificed.…”
Section: Methods Detailsmentioning
confidence: 99%
“…We first tested if 24-h fasting protects mice from seizures using an acute PTZ-induced seizure paradigm (Figure 1A) (Yuskaitis et al, 2021). Fasting for 24 h significantly reduced PTZ-induced seizures from 56% having seizures in the fed state to 22% in fasted mice (Figure 1B).…”
Section: Acute Fasting Protects From Seizures and Reduces Mtor Activi...mentioning
confidence: 99%